1989
DOI: 10.1177/000331978904001210
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Effects of Nifedipine in Patients with Primary Hyperparathyroidism: Case Reports

Abstract: Nifedipine was administered orally to 2 patients with primary hyperparathyroidism before and after parathyroidectomy. The operation lowered serum calcium concentration and parathyroid hormone but did not alter plasma renin activity, plasma aldosterone concentration, and serum magnesium. The hypotensive effects of nifedipine were markedly enhanced with the decrease in serum calcium concentration following parathyroidectomy. Thus, the level of serum calcium concentration may modulate the hypotensive effect of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, clinical examination of the plasma renin activity (PRA) and aldosterone secretion (ALD) in PHPT resulted in contradictory data, i.e. some investigators found no change in the basal values of PRA and ALD (2)(3)(4)(5) and in the responses given to angiotensin II stimulation (6), while others measured increased values which reverted to normal following parathyroidectomy (7)(8)(9). No data were found in the literature regarding the changes in PRA during a stimulation test by volume depletion and orthostasis in PHPT patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical examination of the plasma renin activity (PRA) and aldosterone secretion (ALD) in PHPT resulted in contradictory data, i.e. some investigators found no change in the basal values of PRA and ALD (2)(3)(4)(5) and in the responses given to angiotensin II stimulation (6), while others measured increased values which reverted to normal following parathyroidectomy (7)(8)(9). No data were found in the literature regarding the changes in PRA during a stimulation test by volume depletion and orthostasis in PHPT patients.…”
Section: Introductionmentioning
confidence: 99%